2013
DOI: 10.1093/cid/cit231
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni Infections Associated With Unpasteurized Milk—Multiple States, 2012

Abstract: In 2012, a multistate outbreak of Campylobacter infections associated with unpasteurized milk resulted in 148 illnesses. A dairy with a Pennsylvania Department of Agriculture unpasteurized milk permit and minimal deficiencies identified during inspection was the outbreak source, demonstrating the ongoing hazards of unpasteurized dairy products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 5 publications
1
21
0
2
Order By: Relevance
“…Unpasteurized milk sourced from dairy cattle has also been implicated in a number of campylobacteriosis outbreaks (380)(381)(382). The number of outbreaks in the United States associated with unpasteurized milk increased from 30 in 2007 to 2009 to 51 in 2010 to 2012 (383).…”
Section: Other Sourcesmentioning
confidence: 99%
“…Unpasteurized milk sourced from dairy cattle has also been implicated in a number of campylobacteriosis outbreaks (380)(381)(382). The number of outbreaks in the United States associated with unpasteurized milk increased from 30 in 2007 to 2009 to 51 in 2010 to 2012 (383).…”
Section: Other Sourcesmentioning
confidence: 99%
“…Karagiannis et al [5] reported a C. jejuni outbreak in Crete in which most cases originated from rural areas and had a strong epidemiological evidence that tap water was the vehicle of the outbreak. Longenberger et al [22] reported a multistate outbreak of Campylobacter infections was associated with unpasteurized milk in US which resulted in 148 illnesses. Taylor et al [23] reviewed reports of campylobacteriosis in US from 1997 to 2008 where 262 outbreaks with 9135 illnesses, 159 hospitalizations and 3 deaths were recorded.…”
Section: Although 14 Campylobacter Species Have Been Identified In Tmentioning
confidence: 99%
“…Outbreaks of Campylobacter infection associated with drinking unpasteurized milk are well documented [29,30]. Similarly, small outbreaks of campylobacteriosis within farming families associated with drinking raw milk originating from their farm are frequently reported [31,32].…”
Section: Epidemiological Aspectsmentioning
confidence: 99%